The Role of Scout Organizations in Formation of Leadership Character in Students at SMA Negeri 1 Pagaralam - Achmad Septian Meraksa; Eka Rita Permata Patricia; Syarifuddin Syarifuddin; Aulia Novemy Dhita (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
The development of Scout organizations in Indonesian schools helps form leadership character for students and benefits their lives. This article discusses how the role of scout organizations in shaping leadership character in SMA Negeri 1 Pagaralam; This research was conducted at SMA Negeri 1 Pagaralam. Researchers used qualitative research methods, namely, using interview techniques as a data collection technique to describe what was happening in the field. The results showed that the scout organization played an essential role in forming leadership character, especially for students. The results also show that scouting organizations are essential in schools because it is a place for students to form leadership characteristics that are not easy to do individually. The findings of this study recommend that the Scout organization be preserved in school life, not only in SMA Negeri 1 Pagaralam but also in other schools in Indonesia.